O trabalho do assistente social no fio da navalha: a cena das aparências e a performatividade - Martins, Valter (2015)
In the last three decades, the changes in the international scenery have resulted in severe changes to the state, to social policies and to the social workers labor market. The profession has undergone substantial changes with the reorganization of the State organizations and with the outlines that the new social policies have printed on the attention to social needs. The scope of neoliberal ideas prints a set of new determinations to the daily work of social workers, through new designs of social policies. Despite the expansion of the labor market, the profession has suffered a theoretical-operative redirection in related socio-occupational areas, especially with the implementation of the Bolsa Família Program (BFP) and the Social Welfare policy. The BFP introduces a set of instrumental determinations to work at the State level, the result of management's views that the state has taken in this neoliberal scenario. Thus, this thesis analyzes the roots of the changes that occur in the logic of work in today's society and its consequences for the work of social workers who work in the Social Assistance Reference Centers (SARC) and the BFP operational components. Furthermore, this thesis also considers the daily work, the professionalism, competencies, attributes and the daily answers formulated in these socio-occupational spaces. As objective, it aims to analyze the conception and the outlines of social workers work, unraveling the theoretical and methodological resources mobilized to meet the challenges of everyday life, the determinations of management technologies at work, and how these new ways of operating shape professional answers developing and imposing new powers, duties and / or restrictions to work. In this sense, the thesis presents a contribution to the debate about the work of social workers in the context of social policies, especially under the particularities assumed in the scope of the BFP